Comparison of in vitro and in situ genotoxicity in the Danube River by means of the comet assay and the micronucleus test - Böttcher, Melanie; Grund, Stefanie; Keiter, Steffen; Kosmehl, Thomas; Schweizer, Nadja; Rocha, Paula Suares; Braunbeck, Thomas (Mutation research. Genetic toxicology and environmental mutagenesis, 2010)
Genotoxicity can be correlated with adverse reproductive effects or may even result in elevated extinction risk for particular species of an ecosystem. It may thus be a valuable tool for screening of pollution and potential environmental harm. Since many genotoxicants tend to adsorb onto particulate matter, sediments and suspended materials are of particular interest for genotoxicity screening under field conditions. In order to correlate the genotoxic potential of sediments with genetic damage in fish, rainbow-trout liver (RTL-W1) cells were exposed in vitro to acetone extracts of sediments collected at 10 selected sites along the upper Danube River and analyzed in the comet and micronucleus assays. These in vitro results were compared with micronucleus formation in erythrocytes of the European barbel (Barbus barbus) caught in the field. The two in vitro bioassays showed excellent correlation, indicating comparability of genotoxic potentials in vitro. Sampling sites could be clearly differentiated with respect to severity of effects, with Rottenacker as the most heavily contaminated site, Ehingen and Schwarzach as moderately genotoxic, and with the weakest effects in the tributary Lauchert. All other sediment extracts showed intermediate genotoxic or clastogenic effects. In situ, micronucleus formation in barbel erythrocytes indicated severe genotoxicity at Rottenacker, moderate effects at Ehingen, but minor contamination at Riedlingen and Sigmaringen. In situ observations thus showed excellent correlation with corresponding in vitro tests and document the ecological relevance of in vitro studies with sediment extracts. With respect to the ecological status of the Danube River, the results overall indicate a moderate to severe genotoxic potential with a highly differential localization.
Gesehen am 19.05.2017